NUCLEATION ENVIRONMENT OF DIAMONDS FROM YAKUTIAN KIMBERLITES - Bulanova G.P.; Griffin W.L.; Ryan C.G. (My University, 1998)
The micro-inclusions located in the genetic centre of Yakutian diamond monocrystals have been studied using optical (anomalous birefringence, photoluminescence, cathodoluminescence) and microanalytical (electron-microprobe, proton-microprobe, scanning electron microscope) methods. Most diamonds nucleated heterogeneously on mineral seeds, that lowered the energy barrier to nucleation. Nucleation of peridotitic diamonds occurred on a matrix of graphite+iron+wüstite, in an environment dominated by forsteritic olivine and Fe-Ni sulfide. Nucleation of eclogitic diamonds occurred on a matrix of sulfide ± iron in an environment dominated by Fe-sulfide and omphacite (+/-K-Na-Al-Si-melt). The mineral assemblages recorded in the central inclusions of Yakutian diamonds indicate that they grew in a reduced environment, with oxygen fugacity controlled by the iron-wüstite equilibrium. Nucleation of diamond occurred in the presence of a fluid, possibly a volatile-rich silicate melt, highly enriched in LIL (K, Ba, Rb, Sr) and HFSE (Nb, Ti, Zr) elements. This fluid also carried immiscible Fe-Ni-sulfide melts, and possibly a carbonatitic component; the introduction of this fluid into a reduced refractory environment may have been accompanied by a thermal pulse, and may have created the conditions necessary for the nucleation and growth of diamond.